(Methylcarboxymethylene)tripropylphosphorane: A Stabilized Ylide for Rapid Formation of Methyl Vinyl Ketones and Applications in Medicinal Chemistry and Natural Product Synthesis - Saliba, Paul; Hurem, David; Begovic, Lila; McNulty, James (Synlett, 2025)
The synthesis of (methylcarboxymethylene)tripropylphosphorane, a new air-, water- and light-stable phosphonium ylide for the rapid formation of methyl vinyl ketones from various aldehyde starting materials is reported. This stabilized ylide provides high reaction yields and an excellent degree of E/Z stereoselectivity (>20:1). Furthermore, removal of phosphine oxide is accomplished during aqueous work-up, thus bypassing the need for column chromatography. The versatility of this ylide is demonstrated by the synthesis of methyl vinyl ketones from aryl as well as sensitive enolizable and functionalized aliphatic aldehydes, along with applications of these in the synthesis of olivetol, olivetolic acid, hygroline, and hygrine.
Keywords: Wittig reactions; olefination; stabilized ylides; enones; methyl vinyl ketone; polyketides; alkaloids